TEACHER’S CAPACITY MANAGEMENT TECHNIQUES FOR IMPROVED EDUCATIONAL OUTCOME AMONG PRIVATE AND PUBLIC SECONDARY SCHOOL STUDENTS IN NIGERIA - Eseyin, Emmanuel Olorunleke (IJIET (International Journal of Indonesian Education and Teaching), 2022)
The study investigated teacher’s capacity management techniques for improved educational outcome of private and public secondary school students in Nigeria. Design of the study was analytical survey and correlation. There were 297 private secondary school teachers in and 258 public secondary school teachers in approved secondary schools in Nigeria who served as respondents for the study. The results of the study showed private secondary school teachers differ from public teachers in capacity monitoring, capacity analysis, capacity tuning, capacity planning and demand management for student’s improved educational outcome. There was also a significant relationship between these variables. It was concluded that capacity monitoring contributed to student’s educational outcome and as such capacity management training was recommended for these teachers.